A comparison of spot urinary protein-creatinine ratio with 24-hour urine protein in quantification of proteinuria in women with hypertensive disorders of pregnancy - Chaudhary, Ankita; Agarwal, Divyansh; Agarwal, Rashmi; Agarwal, Sanjay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Proteinuria is a major indicator of hypertensive disorder of pregnancy. The gold standard for diagnosis of significant proteinuria is based on a 24hour urine collection which is cumbersome, time-consuming, and inconvenient to patients. A need, therefore, exists for a rapid, valid, and accurate test to identify significant urinary proteinuria. Methods: We conducted an observational cross-sectional hospital-based study wherein a total of 150 pregnant women who met the criteria of preeclampsia were taken. Spot urine samples for calculating the urine P/C ratio were taken immediately before 24hr urine collection. Correlation between 24hour urine protein and spot PCR was then determined by Pearson’s correlation coefficient(r). Results: The correlation coefficient (r) between 24hr urine protein and spot PCR was found to be 0.734 (n=150) which was highly significant with p<0.001. In this study, population the ROC curve analysis revealed the sensitivity of 90.3% and specificity of 97.3% with AUC 0.958 for a cut-off value of spot PCR as 0.43 to detect significant. Conclusions: Spot PCR is an accurate, valid, steady fast, reliable, and time-saving test which may be used as an alternative method for determining significant proteinuria in patients with pregnancy-induced hypertension.